Capital market development and saving-investment correlation in the Caribbean - Iyare, Sunday Osaretin ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2004)
Examines saving-investment correlations in five Caribbean countries viz. Grenada, Guyana, Jamaica, St. Vincent and the Grenadines and Trinidad and Tobago, using annual time series data for the period 1977-1999.